Pendekatan Content and Language Integrated Learning (CLIL) dalam Pembelajaran Qawāʿid melalui Kitab Kuning di Pesantren - Salma Salsabila; Maman Abdurahman; Shofa Musthofa Khalid; Muhamad Al Bani (Jurnal Internasional Pendidikan Bahasa Arab, 2025)
This study is grounded in the importance of integrating language and content learning in qawāʿid instruction through yellow books in Islamic boarding schools, which naturally reflects the principles of the CLIL approach. It aims to examine how teachers integrate grammar learning with content understanding and how they adapt CLIL principles to address students' varying language proficiencies. This study employed a qualitative approach with a case study design, using classroom observations, interviews with teachers and students, and documentation analysis to explore the implementation of CLIL in qawāʿid instruction. The findings reveal that qawāʿid are not taught separately, but rather embedded within the study of classical Arabic texts, enabling students to engage with both language and content simultaneously. Teachers apply practical strategies such as utilizing texts like Naḥw Taṭbīqī, conducting Arabic-based assessments, and implementing scaffolding, differentiation, and specialized programs like Takhassus. These practices reflect CLIL's cognitive and communicative dimensions. Although the term CLIL is not explicitly used, its principles are contextually embedded in teaching practices. The novelty of this study lies in demonstrating that traditional pesantren pedagogy aligns with modern CLIL theory. It suggests that further theoretical development of CLIL should consider its natural applicability in classical Islamic educational settings.